RUBIES Reveals a Massive Quiescent Galaxy at z = 7.3 - Andrea Weibel; Anna de Graaff; David J. Setton; Tim B. Miller; Pascal A. Oesch; Gabriel Brammer; Claudia D. P. Lagos; Katherine E. Whitaker; Christina C. Williams; Josephine F.W. Baggen; Rachel Bezanson; Leindert A. Boogaard; et al. (The Astrophysical Journal)
We report the spectroscopic discovery of a massive quiescent galaxy at z _spec = 7.29 ± 0.01, just ∼700 Myr after the big bang. RUBIES-UDS-QG-z7 was selected from public JWST/NIRCam and MIRI imaging from the PRIMER survey and observed with JWST/NIRSpec as part of RUBIES. The NIRSpec/PRISM spectrum reveals one of the strongest Balmer breaks observed thus far at z > 6, with no emission lines but tentative Balmer and Ca absorption features, as well as a Lyman break. Simultaneous modeling of the NIRSpec/PRISM spectrum and NIRCam and MIRI photometry (spanning 0.9–18 μ m) shows that the galaxy formed a stellar mass of log $(M_{* }/M_{\odot })=10.2{3}_{-0.04}^{+0.04}$ before z ∼ 8 and ceased forming stars 50–100 Myr prior to the time of observation, resulting in $log({{\rm{sSFR/Gyr}}}^{-1})\lt -1$ . We measure a small physical size of $20{9}_{-24}^{+33}\,{\rm{pc}}$ , which implies a high stellar-mass surface density within the effective radius of $log({{\rm{Σ }}}_{* ,{\rm{e}}}/M_{\odot }\,{{\rm{kpc}}}^{-2})=10.8{5}_{-0.12}^{+0.11}$ , comparable to the highest densities measured in quiescent galaxies at z ∼ 2–5. The 3D stellar-mass density profile of RUBIES-UDS-QG-z7 is remarkably similar to the central densities of local massive ellipticals, suggesting that at least some of their cores may have already been in place at z > 7. The discovery of RUBIES-UDS-QG-z7 has strong implications for galaxy formation models: the estimated number density of quiescent galaxies at z ∼ 7 is >100 ×  larger than predicted from any model to date, indicating that quiescent galaxies have formed earlier than previously expected.